2016
DOI: 10.1016/j.rmed.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive screening for pulmonary hypertension in idiopathic pulmonary fibrosis

Abstract: Background Pulmonary hypertension (PH) is a common complication of idiopathic pulmonary fibrosis (IPF) that is associated with poor prognosis. Noninvasive screening for PH in IPF patients is challenging and a combination of several noninvasive determinations can improve discrimination. Methods We included 235 IPF patients who underwent right heart catheterization (RHC) as part of the lung transplant evaluation. We measured electrocardiographic (ECG) and echocardiographic variables as well as the pulmonary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…We have demonstrated that the CT‐determined PA:A significantly correlates with mPAP as determined by RHC in patients with IPF at initial evaluation. The major strength of our study is that we included a large cohort of patients with IPF, similar to other recently published studies . We demonstrated that the PA:A, %DL CO and 6MWD were independent explanatory variables of elevated mPAP.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…We have demonstrated that the CT‐determined PA:A significantly correlates with mPAP as determined by RHC in patients with IPF at initial evaluation. The major strength of our study is that we included a large cohort of patients with IPF, similar to other recently published studies . We demonstrated that the PA:A, %DL CO and 6MWD were independent explanatory variables of elevated mPAP.…”
Section: Discussionsupporting
confidence: 69%
“…The major strength of our study is that we included a large cohort of patients with IPF, similar to other recently published studies. 27,28 We demonstrated that the PA:A, %DL CO and 6MWD were independent explanatory variables of elevated mPAP. A cut-off value of 0.9 was optimal to predict mPAP > 20 mm Hg and patients with a PA:A > 0.9 had a worse prognosis than those with a PA:A ≤ 0.9.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The relationship was significant, which is in line with previous reports [62][63][64][65]. However, in our study, PA size and PA:A ratio did not show a significant correlation with 6MWD, and, from this perspective, they may not serve as surrogates for RHC for the assessment of exercise capacity, until further, larger studies are obtained.…”
Section: Discussionsupporting
confidence: 90%